Electrical properties of bismuth germanate (Bi 2 GeO 5 ) ferroelectric glass-ceramics prepared by two different methods - Surapong Panyata (2019)
© 2019, © 2019 Taylor & Francis Group, LLC. Ferroelectric Bi 2 GeO 5 glass-ceramics were fabricated using conventional and incorporation method. Glasses have been prepared from BiO 1.5 -GeO 2 -BO 1.5 ternary glass system by focusing on the region of 59 mol%BiO 1.5 : 23 mol%GeO 2 : 18 mol%BO 1.5 . The resulting glass was analyzed by using differential thermal analysis (DTA) for determining the crystallization temperature (T p ). Then, the prepared glass pieces were heat treated at T p . Effects of different fabrication methods on structure and electrical of the glass-ceramics were investigated. X-ray diffraction result of all glass-ceramics suggested that the main peak of glass-ceramics matched the orthorhombic structure of the pure Bi 2 GeO 5 phase. Microstructures of the prepared glass-ceramics have been found to change from rod-like crystallites to bulk crystallites on modifying the fabrication method. The Bi 2 GeO 5 glass-ceramics prepared by incorporation method presented higher dielectric constant than those of the Bi 2 GeO 5 glass-ceramics prepared by conventional method. Moreover, the Bi 2 GeO 5 glass-ceramic prepared by incorporation method possesses a large value of P max (0.94 µC/cm 2 ) comparing to that of the glass-ceramics prepared by conventional method (P max = 0.73 µC/cm 2 ). Thus, this study suggests that the incorporation method can effectively modify the microstructure of Bi 2 GeO 5 glass-ceramics, resulting in the improvement of dielectric and ferroelectric properties.